ACADEMIC AFFAIRS EFFICIENCIES OF SCHOOLS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Promkong , Aongart; Kaenin, Theeraphong (Journal of MCU Nakhondhat, 2023)
This research aims to 1) Investigate the efficiencies of school academic affairs as perceived by teachers 2) To make comparisons of the efficiencies of school academic affairs as perceived by teachers in relevance to their gender, work experience, age, educational degree, school size, and their administrator’s gender 3) To examine problems and suggestions regarding school academic affairs, the thesis is Quantitative Research, The study sample consisted of 335 school teachers under Nakhon Si Thammarat Primary Educational Service Area Office 2, obtained by using Krejcie and Morgan’s, and stratified random sampling. The study instrument was a five-point rating scale questionnaire with the overall reliability coefficient of .989. The data analysis was performed using percentage, frequency, mean, standard deviation, t-test, One-way ANOVA, and Fisher’s Least Significant Difference (LSD) test. The findings revealed that 1) The overall efficiencies and every aspect of school academic affairs as perceived by teachers were found at high levels. When considering in each aspect of school academic affairs; the first mean score was the education measurement and evaluation and the transferring academic performance, the second mean score was the development of learning process and the educational supervision and the third mean score was the research to improve the quality of education 2) The comparison results revealed that there were significant differences at .05 level in teachers’ genders and work experiences, but there were no differences in administrators’ ages, degrees, and work experiences. 3) Problems indicated that some teachers perceived their administrators as being unable to integrate local wisdom, engage parent and community networks in learning management; their integration of learning content, both within and between learning areas, was less than satisfactory.